Physical Reality and Mathematical Description
575 p.
Keywords: This collection of essays is intended as a tribute to Josef Maria Jauch on his sixtieth birthd~. Through his scientific work Jauch has justly earned an honored name in the community of theo retical physicists. Through his teaching and a long line of dis tinguished collaborators he has put an imprint on modern mathema tical physics. A number of Jauch's scientific collaborators, friends and admirers have contributed to this collection, and these essays reflect to some extent Jauch's own wide interests in the vast do main of theoretical physics. Josef Maria Jauch was born on 20 September 1914, the son of Josef Alois and Emma (nee Conti) Jauch, in Lucerne, Switzerland. Love of science was aroused in him early in his youth. At the age of twelve he came upon a popular book on astronomy, and an exam ple treated in this book mystified him. It was stated that if a planet travels around a centre of Newtonian attraction with a pe riod T, and if that planet were stopped and left to fall into the centre from any point of the circular orbit, it would arrive at the centre in the time T/I32. Young Josef puzzled about this for several months until he made his first scientific discovery : that this result could be derived from Kepler's third law in a quite elementary way.